P-wave diffusion in fluid-saturated medium - Ling, C. C. Dennis; Faisal, S. Y.; Zainal, A. A. (Faculty Science, 2010)
This paper considers the propagating P-waves in the fluid-saturated mediums that are categorized to fall into two distinct groups: insoluble and soluble mediums. P-waves are introduced with slowness in accordance to Snell Law and are shown to relate to the medium displacement and wave diffusion. Consequently, the results bear out that the propagating P-waves in the soluble medium share similar diffusive characteristic as of insoluble medium. Nonetheless, our study on fluid density in the mediums show that high density fluid promotes diffusive characteristic whiles low density fluid endorses non-diffusive P-wave